Polysemy and cognition of the verb “ir” in Spanish - Silva Escudero, Gisela (2021)
The polysemy of the verb ir is approached from the cognitive perspective of language. The main objective of the present work is to determine the different senses or meanings of the word ir. It is revealing to define the network of semantic relations of this verb form which, in principle, is associated with physical realities. It is detected that, although there are meanings linked to other domains of reality that are not of a physical order, the metaphorical cognitive mechanisms make possible the conceptualization of different domains as if they were of the material world. Strictly speaking, we detect that a semantic network is formed from a central meaning from which other peripheral meanings radiate.